Помогите решить это :((

  • а)
    раскладывается на множетели группировкой.
    x3+x^2-4x-4=x(x^2-4)+(x^2-4)=(x+1)(x^2-4)
    отсюда 
    x=2;-2;-1 

    б)
    х^4 - 5x^2 - 6 = 0
    замена переменной y= x^2  ; y >=0
    y^2 -5y - 6 =0
    D =25 -4*-6 =49
    y = 1/2 (5 +/- 7)
    y1 = -1  не походит  т.к. 
    y >=0
    y2 = 6 ; x^2 = 6 ; x1 = -√6 ; x2  = √6
    ОТВЕТ x = {-√6 ; √6 }

    в)x² -9 =a
    a² - 8a + 7 = 0
    так как a+b+c =0, то
    a₁ =1
    a₂ = 7
    x² - 9=1
    x² =10
    x₁ = √10
    x₂ = -√10
    x² -9 =7
    x²=16
    x1 = 4
    x2 = -4
    Ответ: 4; -4; √10; -√10

    остальные лень:( 


See also: